A cyclic peptide synthetase gene required for pathogenicity of the fungus Cochliobolus carbonum on maize. - Panaccione, D G (1992)
Specificity in many plant-pathogen interactions is determined by single genes in pathogen and host. The single locus for host-selective pathogenicity (TOX2) in the fungus Cochliobolus carbonum governs production of a cyclic tetrapeptide named HC-toxin. We have isolated a chromosomal region, 22 kilobases (kb) long, that contains a 15.7-kb open reading frame (HTS1) encoding a multifunctional cyclic peptide synthetase. The 22-kb chromosomal region is duplicated in toxin-producing isolates of the fungus but is completely absent from the genomes of toxin-nonproducing isolates. Mutants of the fungus with disruptions in both copies of HTS1, at either of two different sites within HTS1, were engineered by DNA-mediated transformation. Disruption of both copies at either site resulted in loss of ability to produce HC-toxin and loss of host-selective pathogenicity, but the mutants displayed different biochemical phenotypes depending on the site of disruption. The results demonstrate that TOX2 encodes, at least in part, a large, multifunctional biosynthetic enzyme and that the evolution of host range in C. carbonum involved the insertion or deletion of a large piece of chromosomal DNA.